Intellectual Capital (IC) Determinants: Impact on Productivity of Islamic Banks - Ab. Aziz, Muhammad Ridhwan; Meor Hashim, Ahmad Azwan (Binus Business Review, 2017)
This research aimed to investigate the relationship between the Intellectual Capital (IC) efficiency empirically. It consisted of human capital, structural capital, capital employed, and relational capital with the impact on the productivity of Islamic banks in Malaysia. The Pulicâs Value-Added Intellectual Coefficient (VAIC) method with the extended and modified version introduced by former scholars was used to measure IC, whereas bank productivity was measured through Assets Turnover Ratio (ATO). Three internal factors that might have determinants effect on VAIC, namely bank size, bank risks, and leverage were further tested to find their relationship. Structural stability tests and dynamic regression models for panel data were also used for the data of 16 Islamic banks in Malaysia from 2009 to 2016. The panel-corrected standard errors estimation technique was used to estimate a panel regression model with bank productivity and VAIC as the dependent variables. The regression analysis suggests that Malaysian Islamic banks are depending heavily on the capital employed component of intellectual capital, followed by human capital, structural capital, and relational capital. The results also suggest that bankâs risks and leverage play a major role in determining intellectual capital. The findings may serve as a useful input for Islamic bankers to indicate whether the contribution of intellectual capital and its components needs further improvement which it has produced the best results, and internal factor might affect IC.